Emanuelle enchanted (or a description of this world as if it were a beautiful place) - Avery, John (Forced Entertainment, 1992)
Five performers present a jumbled fragmented account of "a strange night that the rain stopped" ... night of urban panic, political crisis and personal reflection. As its central methodology, the piece uses the act of arranging and rearranging texts, images and spaces so that new patterns, narratives and meanings emerge